Application of a nickel-based catalyst in hydroreforming process
The nickel-based catalyst is prepared by the impregnation method, and the inadequate application of nickel-solid acid catalytic system in the prior art is solved, and the efficient hydrogenation reforming of polyolefins and light alkanes is achieved, and the product has high octane number and stable catalytic properties are achieved.
Patent Information
- Application Number
- CN202410027858.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-01-09
AI Technical Summary
In the prior art, the bifunctional catalytic system of nickel-solid acid has not been widely used in the catalyst application process for hydrogenation reforming polyolefins, resulting in low conversion efficiency of waste plastics and light alkanes.
The nickel-based catalyst is prepared by impregnation method. Through hydrothermal reaction and reduction reaction, the nickel is dispersed on the surface of the niobium oxide support to form an efficient catalyst for use in the hydrogenation reforming process.
High-efficiency hydrogenation reforming of polyolefin plastics and light alkanes is achieved. The catalytic product is liquid alkanes with high octane numbers. The catalytic performance is better than that of similar catalysts, and the active components are stable, which is suitable for multiple reaction recovery and regeneration.
Smart Images

Figure CN117884137B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of waste plastics and light alkane hydrogenation reforming, and relates to the application of a nickel-based catalyst in a hydrogenation reforming process. Background Art
[0002] At present, the consumption of plastic products is astonishing, but the average service life is short, causing environmental pollution and huge waste of resources. With the increasing scarcity of oil resources and people's increasing attention to environmental issues, the recycling and resource utilization of waste plastics have become more and more urgent. The main methods for treating waste plastics are landfill, incineration and chemical recovery. The landfill method is simple and economical, but it is easy to cause secondary pollution; the incineration method can obtain heat energy for secondary use, but it will produce harmful substances; the hydrocracking in the chemical recovery method not only solves the pollution problem, but also eases the tension of oil resources. Since the last century, nickel metal catalysts have been used for hydroreforming. Nickel metal catalysts are non-precious metals, with low catalyst costs, and can increase the depth of reforming reactions and increase the yield of gasoline, aromatics and hydrogen. Therefore, the process of using nickel-based catalysts to carry out alkane hydroreforming, light alkane isomerization, alkane dehydrogenation and other processes to improve the octane number of hydrocarbon compounds can produce high-octane hydrocarbons from gasoline to aviation fuel. The isomerization of light alkanes can not only produce high-octane isomerized oil, providing excellent blending components for improving gasoline composition, but also the obtained isomerized hydrocarbons can be further dehydrogenated to produce isomerized olefins, providing raw materials for the production of MTBE, etc., thereby alleviating the contradiction between supply and demand of light isomerized olefins.
[0003] The nickel-solid acid bifunctional catalytic system has been widely studied in the conversion of hydrocarbons and plastics. Nickel nanoparticles have good dehydrogenation activity and are cheap and easy to obtain, and solid acids have good acidity. However, there is currently no catalyst application process that combines the two into hydrogenation reforming polyolefins. Summary of the invention
[0004] Problems existing in traditional hydrocarbon and plastic conversion processes. A new type of nickel-based catalyst and its application in hydroreforming process are proposed.
[0005] In order to achieve the above object, the present invention is implemented by adopting the following technical solutions:
[0006] Application of a nickel-based catalyst in a hydroreforming process, wherein the hydroreforming process is hydroreforming of straight-chain normal alkanes and / or hydroreforming of waste plastics;
[0007] The steps for preparing the nickel-based catalyst are as follows: firstly, dissolving a niobium source and an additive in ultrapure water, adding an ammonium source for hydrothermal reaction, filtering and drying after the hydrothermal reaction, and calcining to obtain a niobium oxide carrier; then, using an impregnation method to load a nickel salt on the surface of the niobium oxide carrier, and performing a reduction reaction to obtain a catalyst.
[0008] Preferably, the impregnation method comprises the following steps: dissolving the nickel salt in deionized water, adding the nickel salt dropwise to the carrier, stirring for 10-60 minutes, and then drying; and the reduction reaction process comprises reducing the nickel salt at 200-600° C. for 3-4 hours under a hydrogen atmosphere.
[0009] Preferably, the niobium source is any one or more of niobium oxide, niobium pentachloride, niobium oxalate, ammonium niobium oxalate, and niobium hydroxide; the additive is any one or more of metal nitrates, metal hydrochlorides, or metal organic salts of aluminum, cerium, nickel, titanium, and zirconium; and the mass fraction of the additive to the niobium source is 0-20%.
[0010] Preferably, the ammonium source is ammonia water or any one or more of ammonium nitrate, hydrochloride, sulfate, organic salt, etc.; the nickel salt is any one or more mixture of nickel nitrate, hydrochloride, sulfate, organic salt, and the mass of nickel ions in the nickel salt accounts for 0.1-20% of the weight of the niobium oxide carrier.
[0011] Preferably, the hydrothermal temperature is 100-260°C, the time is 1-96h, the calcination temperature is 200-600°C, the calcination time is 4h, and the reduction reaction temperature is 200-600°C.
[0012] Preferably, the hydroreforming process is C 6-20 Hydroreforming of alkanes, polyethylene and / or polypropylene.
[0013] Preferably, the reactor is a kettle reactor, the raw material is polyethylene and / or polypropylene, the reaction temperature is 200-350°C, the reaction atmosphere is hydrogen, and the pressure is 0.1-5MPa.
[0014] As a preferred embodiment, the reactor is a fixed bed reactor, and the raw material is C 6-20 Alkanes, reaction temperature is 200-400℃, reaction atmosphere is hydrogen, pressure is 0.1-5 MPa, mass space velocity of raw materials is 1-10 h -1 , the mass ratio of hydrogen to raw material is (5-50):1.
[0015] The catalyst of the present invention is prepared by an impregnation method. The present invention can effectively control the dispersion of metal nickel on the surface of the carrier, and obtain the catalyst after drying and reduction. Finally, the prepared catalyst is applied to the reaction of polyolefin plastics with light alkanes (C 6-12 The catalytic product of the hydroreforming of polyolefin waste plastics and light alkanes is a high-octane liquid alkane, and its catalytic performance is better than that of similar catalysts. It provides a new way for the hydroreforming of polyolefin waste plastics and light alkanes.
[0016] Compared with the prior art, the advantages and positive effects of the present invention are:
[0017] 1. The nickel-based catalyst prepared in the present invention has a very high catalytic activity, and under the same conditions, the catalytic activity is close to or even exceeds that of some precious metal catalysts.
[0018] 2. In the hydrogenation reforming reaction of polyolefin plastics, the catalyst of the present invention has an effect on C 5-20 Liquid fuels showed the best selectivity for C 5-20 The selectivity for highly branched hydrocarbons is greater than 90%.
[0019] 3. The catalyst prepared by the present invention has a strong metal-support interaction, so the active components are stable and not easily lost during the reaction. After multiple reactions and recycling, the catalyst performance can still maintain about 90% of the initial performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the TEM characterization image of the catalyst prepared in Example 1.
[0021] Figure 2 This is the XRD characterization diagram of the catalyst prepared in Example 1.
[0022] Figure 3 This is the product selectivity distribution diagram of the catalytic conversion of polyethylene by nickel-based catalysts.
[0023] Figure 4 This is the product distribution diagram of hexane hydroreforming over nickel-based catalyst.
[0024] Figure 5 This is the product distribution diagram of dodecane hydroreforming over nickel-based catalyst.
[0025] Figure 6 The ammonia adsorption and desorption comparison between Example 1 and Comparative Examples 1, 2, and 3 is shown.
[0026] Figure 7 This is the infrared comparison of pyridine of Example 1 and Examples 3 and 5. DETAILED DESCRIPTION
[0027] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0029] Example 1
[0030] Weigh 20g niobium oxide and 3g zirconium sulfate in a beaker, add 50ml ultrapure water and start stirring (600 rpm, the same below), drop 20ml of 1mol / L ammonia water during stirring, and control the dropping time to 2-5 min. Then transfer all the solution to a hydrothermal reactor, hydrothermally react at 200℃ for 24h, filter at room temperature, wash the solid with 1L deionized water, and then place it in an oven at 80℃ to dry for 8h, and then calcine at 400℃ for 4h to obtain a niobium zirconium oxide carrier. Then, dissolve 0.5g nickel nitrate in 2g ultrapure water, and after dissolving evenly, add dropwise to a beaker containing 5g of the carrier and stir manually with a glass rod for 15min, then dry it in an oven at 80℃ for 12h. After drying, add it to a tube furnace and heat it to 400℃ at 2 degrees per minute, reduce it in a hydrogen atmosphere for 3h, and naturally cool it to room temperature to obtain a catalyst.
[0031] The catalyst prepared in this example was dispersed in an ethanol solution and characterized by TEM. The results are as follows Figure 1 ,from Figure 1 It can be seen that the catalyst nickel nanoparticles prepared in this example are uniformly loaded on the surface of the catalyst.
[0032] The catalyst prepared in this example was characterized by XRD. Figure 2 ,from Figure 2 It can be seen that the catalyst did not change the crystal form of the carrier during the preparation process.
[0033] Polyethylene (molecular weight 12k) was added to the autoclave reactor, the reaction temperature was 270 degrees Celsius, the reaction time was 5 hours, and the hydrogen pressure was 3 MPa; the product selectivity distribution was obtained as follows Figure 3 ,from Figure 3 It can be seen that the product of polyethylene hydroreforming is mainly gasoline C 5-12 , there are more isomerization products and they have higher economic value.
[0034] Example 2
[0035] The preparation method and application of the catalyst are the same as those in Example 1. Reaction conditions: n-hexane is introduced into a fixed bed reactor, the reaction temperature is 215 degrees Celsius, the sampling time is 10 hours, the reaction hydrogen pressure is 2 MPa, the mass space velocity (WHSV) of the raw material is 5, and the mass ratio of hydrogen to raw material is 15:1.
[0036] The catalyst prepared in this example was used to hydrogenate n-hexane to obtain a product selectivity distribution diagram. The results are as follows: Figure 4 ,from Figure 4 It can be seen that the product after hexane hydroreforming is mainly isomerized hexane, which proves that the catalyst has good hydroreforming ability.
[0037] Example 3
[0038] The present embodiment is consistent with the embodiment 1 unless otherwise specified.
[0039] Weigh 20g of niobium pentachloride and 3g of aluminum nitrate in a beaker, add 50ml of ultrapure water and start stirring (600 rpm, the same below), drop 20ml of ammonium nitrate with a concentration of 1mol / L during stirring, and control the dropping time to 2-5 min. Then transfer all the solution to a hydrothermal reactor, hydrothermally react at 200℃ for 24h, filter at room temperature, wash the solid with 1L of deionized water, and then place it in an oven at 80℃ to dry for 8h, and then calcine at 400℃ for 4h to obtain a niobium aluminum oxide carrier. Then, 0.5g of nickel acetate was dissolved in 2g of ultrapure water, and after uniform dissolution, it was added drop by drop into a beaker of 5g of the carrier and manually stirred with a glass rod for 15min, and then dried in an oven at 80℃ for 12h. After drying, it was added to a tubular furnace and heated to 400℃ at 2 degrees per minute, reduced for 3h in a hydrogen atmosphere, and naturally cooled to room temperature to obtain catalyst No. 2. Reaction conditions: polyethylene was added to a kettle reactor, the reaction temperature was 270 degrees Celsius, the reaction time was 5 hours, and the reaction hydrogen pressure was 3 MPa.
[0040] Example 4
[0041] The preparation method and application of the catalyst are the same as those in Example 3. Reaction conditions: dodecane is introduced into a fixed bed reactor, the reaction temperature is 215 degrees Celsius, the sampling time is 10 hours, the reaction hydrogen pressure is 2 MPa, the mass space velocity (WHSV) of the raw material is 5, and the mass ratio of hydrogen to raw material is 15:1.
[0042] The catalyst prepared in this example was used to hydrogenate dodecane to obtain a product selectivity distribution diagram. The results are as follows: Figure 5 ,from Figure 5 It can be seen that the product after hexane hydroreforming is mainly isomerized dodecane, which proves that the catalyst has good hydroreforming ability.
[0043] Example 5
[0044] Weigh 20g of ammonium niobium oxalate and 3g of titanium chloride in a beaker, add 50ml of ultrapure water and start stirring (700 rpm, the same below), drop 20ml of 0.1mol / L ammonium chloride during stirring, and control the dropping time to 2-5 min. Then transfer all the solution to a hydrothermal reactor, hydrothermally react at 200℃ for 24h, filter at room temperature, wash the solid with 1L of deionized water, and then place it in an oven at 80℃ to dry for 8h, and then calcine at 400℃ for 4h to obtain a niobium titanium oxide carrier. Then, 0.5g of nickel chloride was dissolved in 2g of ultrapure water, and after uniform dissolution, it was added drop by drop into a beaker of 5g of the carrier and manually stirred with a glass rod for 15min, and then dried in an oven at 80℃ for 12h. After drying, it was added to a tubular furnace and heated to 400℃ at 2 degrees per minute, reduced for 3h in a hydrogen atmosphere, and naturally cooled to room temperature to obtain catalyst No. 3. Reaction conditions: Add polypropylene into the autoclave reactor, the reaction temperature is 270 degrees Celsius, the reaction time is 5 hours, and the reaction hydrogen pressure is 3 MPa.
[0045] Example 6
[0046] The preparation method and application of the catalyst were the same as those in Example 5. Reaction conditions: a mixture of hexane and argon was introduced into a fixed bed reactor, the reaction temperature was 220 degrees Celsius, the sampling time was 15 hours, the reaction hydrogen pressure was 1.25 MPa, the mass space velocity (WHSV) of the raw material was 5, and the mass ratio of hydrogen to raw material was 25:1.
[0047] Comparative Example 1
[0048] When preparing the catalyst, 20 g of niobium oxide and 4 g of zirconium sulfate (the molar fraction of the additive and the niobium source is 10%) are weighed, and the rest of the preparation process is the same as Example 1. Reaction conditions: polyethylene is added to the autoclave reactor, the reaction temperature is 270 degrees Celsius, the reaction time is 5 hours, and the reaction hydrogen pressure is 3 MPa.
[0049] Comparative Example 2
[0050] The hydrothermal conditions during the catalyst preparation process were changed to an oven at 260 degrees for 96 hours, and the rest of the preparation process was the same as Example 1. Reaction conditions: polyethylene was added to the autoclave reactor, the reaction temperature was 270 degrees Celsius, the reaction time was 5 hours, and the reaction hydrogen pressure was 3 MPa.
[0051] Comparative Example 3
[0052] When preparing the catalyst, 1g of nickel chloride was dissolved in ultrapure water and loaded on the surface of 5g of the carrier by impregnation, that is, the weight ratio of nickel to the carrier in this comparative example was 20%, and the rest of the preparation process was the same as Example 1. Reaction conditions: polyethylene was added to the autoclave reactor, the reaction temperature was 270 degrees Celsius, the reaction time was 5 hours, and the reaction hydrogen pressure was 3 MPa.
[0053] Catalyst performance test: The catalyst obtained in Examples 1 and 2 is recorded as catalyst No. 1, the catalyst obtained in Examples 3 and 4 is recorded as catalyst No. 2, and the catalyst obtained in Examples 5 and 6 is recorded as catalyst No. 3. Among them, catalyst No. 1 was tested for the performance of polyethylene (molecular weight 12k) and hexane hydroreforming in a kettle reactor; catalyst No. 2 was tested for the performance of polyethylene (molecular weight 12k) and hexane hydroreforming in a fixed bed reactor; catalyst No. 3 was tested for the performance of polypropylene (molecular weight 15k) and hexane hydroreforming in a fixed bed reactor.
[0054] The operation process of the tank reactor is as follows:
[0055] (1) Hydrogenation reforming of polyethylene or polypropylene
[0056] Mix 0.2 g of catalyst with 4.0 g of polyethylene or polypropylene and place in a reactor. Fill the reactor with raw gas (hydrogen) at a pressure of 0.1-5 MPa. Gradually increase the reaction temperature to 220-350 degrees Celsius to start the reaction. The reaction time is 1-48 hours to test the catalyst performance. After the reaction is completed, collect the gas and liquid products and conduct corresponding chromatographic analysis.
[0057] (2) Hydrogenation reforming of light alkanes (C 6-12 )
[0058] 0.2 g of catalyst and 4.0 g of light alkane are added into the reactor, and the raw gas (hydrogen) is filled into the reactor with a pressure of 0.1-5 MPa. The reaction temperature is gradually increased to 200-400 degrees Celsius to start the reaction. The reaction time is 1-48 hours to test the catalyst performance. After the reaction is completed, the gas and liquid products are collected and the corresponding chromatographic analysis is performed.
[0059] The product conversion and selectivity were calculated according to the following formula:
[0060] Polyolefin conversion rate = (mass before reaction - mass of solids remaining after reaction) / mass before reaction * 100%.
[0061] Conversion rate of light alkanes = chromatographic peak area after reaction / chromatographic peak area before reaction*100%.
[0062] Product selectivity = product mass / (mass before reaction - mass of remaining solids after reaction)*100%.
[0063] The fixed bed reactor operation process is as follows:
[0064] (1) Hydrogenation reforming of polyethylene or polypropylene
[0065] 0.1 g of catalyst is physically mixed with 2 g of polyethylene or polypropylene and then filled into a quartz tube. The pressure inside the quartz tube is stabilized at 0.1-5 MPa and the mass space velocity (WHSV) of the raw material is 1-10 h -1 The molar ratio of hydrogen to raw material is (0.001-0.1): 1. The reaction temperature is gradually increased to 200-400 degrees Celsius to start the reaction. In the reactor, the temperature is gradually increased. After the reaction is balanced for 1 hour, the product is sampled and the corresponding chromatographic analysis is performed.
[0066] (2) Hydrogenation reforming of light alkanes (C 6-12 )
[0067] The vaporized alkane is introduced into the reactor along with the carrier gas (nitrogen or argon, flow ratio 1 / 8). The pressure in the quartz tube is stabilized at 0.1-5 MPa, and the mass space velocity (WHSV) of the raw material is 1-10h -1 The molar ratio of hydrogen to raw material is (5-50): 1. The reaction temperature is gradually increased to 200-400 degrees Celsius to start the reaction. In the reactor, the temperature is gradually increased. After the reaction is balanced for 1 hour, the product is sampled and the corresponding chromatographic analysis is performed.
[0068] According to the above method, the catalyst performance is shown in Table 1, Table 2 and Table 3.
[0069] surface Conversion comparison of catalysts in Examples 1, 3, and 5
[0070]
[0071] surface Conversion comparison of catalysts in Examples 2, 4, and 6
[0072]
[0073] Table 3 Conversion comparison of Example 1 and comparative catalyst
[0074]
[0075] It can be seen from Table 1 that the catalyst prepared by the present invention can achieve the technical effect of hydrogenation reforming of polyolefins. Taking Example 1 as an example, the polyethylene conversion rate is 100%, and the selectivity of gasoline alkanes is as high as 95.5%. It can be seen from Table 2 that the catalyst prepared by the present invention can also achieve the hydrogenation reforming of light alkanes. Taking Example 2 as an example, the hexane conversion rate is 93.3%, and the selectivity of isomerized substrates is 88.5%. The acidity of the catalyst affects the activity of the catalyst, and then affects the conversion rate of the product. Within the scope of the embodiment, the higher the acidity of the catalyst, the better the catalytic effect. From Tables 3 and Figure 6It can be seen that the preparation conditions of the catalyst have a great influence on the performance of the catalyst. First, the ratio of the additive to the niobium source. Too high or too low a ratio will affect the acidity of the carrier. Second, the change of the hydrothermal conditions of the carrier will also change the acidity of the carrier. The longer the calcination time and the higher the temperature, the weaker the acidity. Third, the nickel loading. The higher the nickel loading, the more it will affect the acidity of the catalyst. Figure 7 It can be seen that the change of the additive has little effect on the acidity of the catalyst. The difference in catalytic performance may be due to the combined effect of niobium, zirconium, aluminum and other metals in the carrier.
[0076] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. Application of a nickel-based catalyst in a hydroreforming process, characterized in that: The hydroreforming process is hydroreforming of straight-chain normal alkanes and / or hydroreforming of waste plastics; The nickel-based catalyst preparation steps are as follows: firstly, dissolving a niobium source and an additive in ultrapure water, adding an ammonium source for hydrothermal reaction, filtering and drying after the hydrothermal reaction, and calcining to obtain a niobium oxide carrier; then, using an impregnation method to load a nickel salt on the surface of the niobium oxide carrier, and performing a reduction reaction to obtain a catalyst; The additive is any one or more of metal nitrates, metal hydrochlorides or metal organic salts of aluminum, cerium, titanium and zirconium; the mass fraction of the additive to the niobium source is 0-20%, and is not 0.
2. The application according to claim 1, characterized in that: The steps of the impregnation method are: dissolving the nickel salt in deionized water, adding it drop by drop into the carrier, stirring for 10-20 minutes, and then drying; the reduction reaction process is to reduce at 200-600° C. for 3-4 hours under a hydrogen atmosphere.
3. The application according to claim 2, characterized in that: The niobium source is any one or more of niobium oxide, niobium pentachloride, niobium oxalate, ammonium niobium oxalate and niobium hydroxide.
4. The application according to claim 2, characterized in that: The ammonium source is any one or more of ammonia water or ammonium nitrate, hydrochloride, sulfate and organic salt; the nickel salt is any one or more mixture of nickel nitrate, hydrochloride, sulfate and organic salt, and the mass of nickel ions in the nickel salt accounts for 0.1-20% of the weight of the niobium oxide carrier.
5. The application according to claim 2, characterized in that: The hydrothermal temperature is 100-260°C, the time is 1-96h, the calcination temperature is 200-600°C, the calcination time is 4h, and the reduction reaction temperature is 200-600°C.
6. The use according to claim 2, characterized in that: The hydroreforming process is C 6-20 Hydroreforming of alkanes, polyethylene and / or polypropylene.
7. The use according to claim 6, characterized in that: The reactor is a kettle reactor, the raw material is polyethylene and / or polypropylene, the reaction temperature is 200-350°C, the reaction atmosphere is hydrogen, and the pressure is 0.1-5MPa.
8. The use according to claim 6, characterized in that: The reactor is a fixed bed reactor, and the raw material is C 6-20 Alkanes, reaction temperature is 200-400℃, reaction atmosphere is hydrogen, pressure is 0.1-5 MPa, mass space velocity of raw materials is 1-10h -1 , the mass ratio of hydrogen to raw material is (5-50):1.
Citation Information
Patent Citations
Catalyst for alkane isomerization, preparation method thereof, and reactor
CN107570182A
Hydrodeoxygenation catalyst and preparation method and application thereof
CN113441140A